Business Coalitions in the Us and Their Role in Advancing a Regional Agenda - Bogdana NEAMTU (Transylvanian Review of Administrative Sciences, 2008)
The analysis herein explores the topic of business coalitions and focuses on the role they may play in advancing a regional agenda. The structure of the paper is threefold: (1) in the introductory section I briefly explain the meaning of the concept and how it relates to other similar concepts such as public-private partnerships or growth coalitions; (2) the second part focuses on analyzing the characteristics that best define contemporary business coalitions and stresses the implications of these characteristics for the structuring or restructuring of traditional local and regional political entities; (3) the last section focuses on how planners and other public officials could use or partner with business coalitions in order to advance their own regional agenda. In the conclusion section I argue that though business coalitions are important for the development of a regional economy and regional identity, it would be a mistake to think that they alone can determine the success of a region. Regional government should continue to be pursued as it represents the only solution to problems such as social and environmental justice, tax sharing, education, and inner city redevelopment.